2020
DOI: 10.3389/fnins.2020.00890
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenine, Tetrahydrobiopterin, and Cytokine Inflammatory Biomarkers in Individuals Affected by Diabetic Neuropathic Pain

Abstract: Neuropathic pain is a common complication of diabetes with high morbidity and poor treatment outcomes. Accumulating evidence suggests the immune system is involved in the development of diabetic neuropathy, whilst neuro-immune interactions involving the kynurenine (KYN) and tetrahydrobiopterin (BH4) pathways have been linked to neuropathic pain pre-clinically and in several chronic pain conditions. Here, using a multiplex assay, we quantified serum levels of 14 cytokines in 21 participants with type 1 diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…Our laboratory demonstrated an increase in serum levels of granulocyte-macrophage colony stimulating factor (GM-CSF) and IL-8 in a similar cohort of DNP patients ( Staats Pires et al., 2020 ). GM-CSF prompts monocytes to differentiate into macrophages ( Boyette et al., 2017 ; Trus et al., 2020 ) and acts on macrophages to release pro-inflammatory mediators that can interact with nociceptors ( Tewari et al., 2020 ).…”
Section: Discussionmentioning
confidence: 88%
“…Our laboratory demonstrated an increase in serum levels of granulocyte-macrophage colony stimulating factor (GM-CSF) and IL-8 in a similar cohort of DNP patients ( Staats Pires et al., 2020 ). GM-CSF prompts monocytes to differentiate into macrophages ( Boyette et al., 2017 ; Trus et al., 2020 ) and acts on macrophages to release pro-inflammatory mediators that can interact with nociceptors ( Tewari et al., 2020 ).…”
Section: Discussionmentioning
confidence: 88%
“…6,11,173,255,277,375,376 Neuroinflammation and specifically proinflammatory cytokines are further critical regulators of neuropathic pain resulting from nerve damage, such as traumatic nerve lesions or complex regional pain syndrome (CRPS), as well as antineoplastic chemotherapies, diabetes, or postherpetic neuralgia. 26,42,148,195,212,303 Emerging evidence supports the idea that cytokines may even be relevant at brain level for the development of mental comorbidities. Depressive mood, cognitive impairment, and sleep disturbance are not only highly prevalent comorbidities in chronic pain disorders but also more generally prevalent in inflammatory diseases, such as RA, where they even contribute to the maintenance and progression of the disease.…”
Section: Introductionmentioning
confidence: 95%
“…Despite the lack of studies showing the role of the kynurenine metabolites in COVID-19 pain, many studies have shown its relationship with neuropathic pain and other painful conditions ( Rojewska et al, 2016 ; Rojewska et al, 2018 ; Staats Pires et al, 2020 ; Jovanovic et al, 2020 ; Ciapała et al, 2021 ; Tanaka et al, 2021 ). Some metabolites can act as immunomodulators depending on the dose or the situation, perpetuating low-grade inflammation ( Tanaka et al, 2020 ).…”
Section: Kynurenine Pathway and Covid-19mentioning
confidence: 99%